Representaciones y narraciones formativas de la alteridad. La subjetividad política como escenario de relación y conflicto. (2019)
This article meets the need of thinking the notion of individual and politics beyond modern rationale framework. To this end, it raises a relational-conflict idea as a requirement for a human existence possibility and on this foundation the political subjectivity is defined as the scenario to construct the alterity in the field of representations and power. Firstly, it gives a broad overview along some modernity traits and its idea of individual, claiming that in the western metaphysics the politics was unthinkable and also showing the way modern hegemony prompts the idea of intersubjectivity as well as a broader political way of thinking. Secondly, it shows how it is possible now to understand historically the birth of subjectivity, in this case, the ambivalence between power as a concept and world power, stating, hence, the possibility for the transfiguration of the individual. In the third place, it explores the representations field in the experience and the otherness dynamics in relation to the consequences of the monolithic idea of the modern individual and the establishment of capitalism. Portraying mainly, the loss of experience and communicative capability, therefore, the loss of the Otherness. Finally, it makes us wonder to what degree narrating individually and collectively in an educational field allows the formation of political subjectivities, the recovery of experience and the acknowledgment of the alterity without undermining the necessity of conflict. 392 ANÁLISIS N.o 95 Edisson Leonardo Parra Herrera It starts with the conceptualization of the conflict from Weber, to know the approach from which the problems were addressed. Likewise, in the theoretical field we opted for an approach from the historical institutionalism to the construction of peace in Colombia.